Software-Based Circle Technology in Dinagat Geometry Class: A Single Subject Research - Jonas Villegas Cuevas; Irmalyn Borja Paymalan (International Journal on Emerging Mathematics Education, 2021)
Present study investigated the effectiveness of the use of technology software-based instruction in learning Circle Geometry, the extent of the students' interest on the use of this strategy, and designs a classification model through Discriminant Analysis forcasting students' performance as to having mastered or not the lessons based on their interest on the use of the strategy. The study utilized single subject research design to the thirty-one Grade 10 students in Llamera National High School, Dinagat Islands Division. Trend analysis and repeated ANOVA results revealed that most students' performance in circle geometry improved throughout the intervention of technology software-based instruction and the gap between the high achieving and low achieving students was reduced. Students also perceived high interest in learning geometry through the intervention. Indeed, technology software-based instruction recuperates knowledge in Circle Geometry. Accordingly, the capability to visualize the lesson through the software-based instruction is the best predictor of the students' mastery in circle geometry.